Effect of Washed Microbiota Transplantation on Patients With Dyslipidemia in South China - Liang, Fenfen; Lu, Xinjian; Deng, Zhiliang; Zhong, Hao-Jie; Zhang, Wei; Li, Qing; Zhou, Hong-Hao; Liou, Yu-Ligh; He, Xing-Xiang (Frontiers in Endocrinology, 2022)
Background and Aims Although the manual crude fecal microbiota transplantation (FMT) reduces blood lipids in animal models of hyperlipidemia, its clinical effect on blood lipid metabolism in patients with hyperlipidemia and hypolipidemia remains unclear, especially in the Chinese population. It was reported that washed microbiota transplantation (WMT) was safer, more precise, and more quality-controllable than the crude FMT by manual. This study aimed to investigate the feasibility and effectiveness of WMT on lipid metabolism in the Chinese population. Methods Clinical data of patients with various indications who received WMT for 1–3 treatment procedures were collected. Changes in blood lipids before and after WMT, namely, total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), homeostasis model assessment of insulin resistance (HOMA-IR), liver fat attenuation, and liver stiffness measurement, were compared. Results A total of 177 patients (40 cases of hyperlipidemia, 87 cases with normal blood lipids, and 50 cases of hypolipidemia) were enrolled in the First Affiliated Hospital of Guangdong Pharmaceutical University. WMT has a significant therapeutic effect in reducing blood lipid levels (TC and TG) in the short- and medium term in patients with hyperlipidemia (p <0.05). Hyper blood lipid decreased to normal in the short-term (35.14%; p <0.001), and LDL-C changed to normal in the medium term (33.33%; p = 0.013). In the hypolipidemia group, 36.36% and 47.06% changed to normal in the short-term (p = 0.006) and medium term (p = 0.005) of therapeutic effects based on blood lipid levels. In the normal blood lipid group and the low-risk group of atherosclerotic cardiovascular disease (ASCVD), the change was not statistically significant, indicating that WMT does not increase the risk of blood lipid and ASCVD in the long-term. Conclusions WMT treatment changes blood lipids in patients with hyperlipidemia and hypolipidemia without serious adverse events, with no risk for increasing blood lipids and ASCVD in the long-term. There were significant decreased TC, TG, and LDL-C levels in the medium term of WMT treatment for hyperlipidemia. Therefore, the regulation of gut microbiota by WMT may indicate a new clinical method for the treatment of dyslipidemia.